Empowering indigenous women in Guatemala: a case study of the role of Digital Community Centers in enhancing digital literacy and changing gender perspectives in Northern Huehuetenango - Ortiz Osejo, Nereyda Y.; Arrechea, Susana; Alvarado, Alejandro (Frontiers in Research Metrics and Analytics, 2025)
IntroductionThis study examines how Digital Community Centers (DCCs) contribute to the empowerment of indigenous Mayan women in Northern Huehuetenango, Guatemala. Although rural and indigenous communities remain largely excluded from digitalization, the DCC model aims to narrow the digital gap by providing internet access, basic computer training, and workshops on positive masculinities.MethodsWe employed a mixed-methods approach, including 10 semi-structured focus groups and 43 surveys. The survey assessed digital literacy and gender attitudes using the GNDR-4 and GEM scales.ResultsFindings show significant improvements in women's digital skills after a short training period. These gains enabled participants to reduce travel time for tasks such as processing government documents and to launch small-scale economic initiatives. Participants who attended the positive masculinity training—both men and women—reported more equitable attitudes toward women's leadership and decision-making.DiscussionDespite these gains, participants stressed ongoing barriers—most notably limited infrastructure, constrained financial resources, and insufficient institutional support—that hamper the long-term viability of the DCCs. They also noted a need for more detailed and standardized training on gender topics to sustain changes in attitudes over time. In conclusion, DCCs offer a promising strategy for bridging the digital divide and facilitating women's socio-economic participation, but further research with larger samples and longer follow-up periods is warranted to confirm and expand upon these initial findings.